A Novel Marker, Based on Ultrasound Tomography, for Monitoring Early Response to Neoadjuvant Chemotherapy. Issue 6 (27th October 2020) - Duric, Neb; Littrup, Peter; Sak, Mark; Li, Cuiping; Chen, Di; Roy, Olivier; Bey-Knight, Lisa; Brem, Rachel
Abstract: Objective: To evaluate the combination of tumor volume and sound speed as a potential imaging marker for assessing neoadjuvant chemotherapy (NAC) response. Methods: This study was carried out under an IRB-approved protocol (written consent required). Fourteen patients undergoing NAC for invasive breast cancer were examined with ultrasound tomography (UST) throughout their treatment. The volume (V) and the volume-averaged sound speed (VASS) of the tumors and their changes were measured for each patient. Time-dependent response curves of V and VASS were constructed individually for each patient and then as averages for the complete versus partial response groups in order to characterize differences between the two groups. Differences in group means were assessed for statistical significance using t -tests. Differences in shapes of group curves were evaluated with Kolmogorov–Smirnoff tests. Results: On average, tumor volume and sound speed in the partial response group showed a gradual decline in the first 60 days of treatment, while the complete response group showed a much steeper decline ( P < 0.05). The shapes of the response curves of the two groups, corresponding to the entire treatment period, were also found to be significantly different ( P < 0.05). Furthermore, large simultaneous drops in volume and sound speed in the first 3 weeks of treatment were characteristic only of the complete responders ( P < 0.05). Conclusion: This study demonstrates the feasibility of using UST to monitor NAC response, warranting future studies to better define the potential of UST for noninvasive, rapid identification of partial versus complete responders in women undergoing NAC.